1991
DOI: 10.1128/mcb.11.7.3564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cis sequences controlling efficient position-independent tissue-specific expression of human major histocompatibility complex class I genes in transgenic mice.

Abstract: We previously reported that genomic major histocompatibility complex class I human leukocyte antigen (HLA)-B7 gene constructs with as little as 0.66 kb of 5'-and 2.0 kb of 3'-flanking DNA were expressed efficiently and appropriately in transgenic mice. To identify and characterize the relevant cis-acting regulatory elements in more detail, we have generated and analyzed a series of transgenic mice carrying native HLA-B7 genes with further 5' truncations or intronic deletions and hybrid constructs linking the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 31 publications
(84 reference statements)
3
34
0
Order By: Relevance
“…A similar result was obtained in the human HLA-B7 gene, in that a truncated HLA-B7 gene lacking the 5Ј promoter region was IFN-inducible when transfected into mouse L cells (20). Further, HLA-B7 expression from constructs that lacked the 5Ј ISRE were up-regulated severalfold by IFN-␥ in transgenic mice (21). In none of these cases was it demonstrated whether IFN stimulation of class I gene expression was due to a transcriptional effect mediated by sequences downstream of the promoter, or by posttranscriptional mechanisms.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…A similar result was obtained in the human HLA-B7 gene, in that a truncated HLA-B7 gene lacking the 5Ј promoter region was IFN-inducible when transfected into mouse L cells (20). Further, HLA-B7 expression from constructs that lacked the 5Ј ISRE were up-regulated severalfold by IFN-␥ in transgenic mice (21). In none of these cases was it demonstrated whether IFN stimulation of class I gene expression was due to a transcriptional effect mediated by sequences downstream of the promoter, or by posttranscriptional mechanisms.…”
supporting
confidence: 61%
“…These observations raised the question of whether sequences other than the 5Ј-flanking region of the HLA-A2 gene could be necessary for IFN-␥ induction. In this regard, studies in both the mouse H-2L gene and the human HLA-B7 gene have shown that sequences located 3Ј to the transcription initiation site are both necessary for full response to IFN-␥ and sufficient to mediate some IFN-␥ response (17,18,21). Our results show that in K562 cells, which had been stably transfected with an HLA-A2 genomic clone containing 525 bp of the 5Ј promoter, all eight exons, and ϳ1300 bp of 3Ј-transcribed region, IFN-␥ stimulation increases the level of RNA from the transfected gene by 3-fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the proteasomes studied here, brain proteasomes normally contain very low levels of LMP2 and LMP7 ␤-subunits compared with liver or spleen (25), presumably because brain also has much lower levels of MHC molecules and is less active in antigen presentation (54). Consequently, any reaction of lactacystin with the three IFN-␥-induced subunits would have been missed in the earlier studies.…”
Section: Role Of the Proteasome In Proteinmentioning
confidence: 56%
“…Investigation of HLA-B7 genes showed the presence of c i s-acting regulatory sequences between -75 to -660, which are responsible for constitutive as well as IFN-γ induced tissue-specific expression of this gene (Chamberlain et al, 1991). Similarly, enhancer A, and B (Figure 1) regions present upstream of class I MHC coding sequence act as a negative element in F9 EC cells.…”
Section: Assembly Of Mhc Class I Moleculementioning
confidence: 99%